Association between VEGF–2578 C>A Gene Polymorphism and Lifestyle in H. Pylori Positive Gastritis Patients - Sinulingga, Mario Eka Paskah; Ilhamd (TALENTA Publisher, Universitas Sumatera Utara, 2021)
Abstract Background: The polymorphisms make the differences in virulence and pathogenicity of H. pylori, which lead to different clinical manifestations after H. pylori infection. The aim research to assess correlation between between VEGF–2578 C>A Gene Polymorphism and life style in H. Pylori (+) Gastritis Patients. Method: The design of this study is a cross sectional study of H. Pylori (+) Gastritis patients, independent variables is gene polymorphism VEGF-2578C>A and dependent variables are life style (age, gender, BMI and alcohol). Infection of H. Pylori detected 14C-UBT or rapid urease test. Examination of gene polymorphism VEGF-2578C>A by performing DNA extraction (Spin Column Method) with reagent: High Pure PCR Template through PCR procedure. Results: From 59 pasien Gastritis H. Pylori (+), there is no correlation between VEGF-2578 C>A gene polymorphism (consisting of CC, CA and AA) with lifestyle (gender, age consists of < 45 years and > 45 years, BMI consists of < 25 kg/m2 and > 25 kg/m2, alcoholic drinkers ) Conclusion: There is no correlation between VEGF–2578 C>A Gene Polymorphism and life style (age, sex, BMI and alcohol drinking) in H. Pylori (+) Gastritis Patients.